Penggunaan Media Dompet VIP untuk Menciptakan Efektifitas Pembelajaran Jarak Jauh - Wahyuni, Popi; Oktavian, Ardi (Jurnal Nispatti, 2025)
This study aims to determine the effectiveness of distance learning using document media, Power Point and Video Learning (VIP WALLET) in PPKN learning for students in grade 9.5 at SMPN 38 Medan for the 2020/2021 academic year. The method used is a classroom action research method which consists of two cycles. Before giving the teaching action using the VIP WALLET media, only 32.14% of students had achieved mastery learning, while 67.86% of students had not yet achieved mastery learning. In the first cycle of learning using the media combined with assignments, it was found that 85.7% of students had achieved mastery learning and as many as 14.29% had not yet achieved mastery learning. In the second cycle of learning using VIP WALLET media combined with assignments, it was found that 95.14% of students had achieved mastery learning and only 4.86% had not yet achieved mastery learning. Based on these data it is concluded that the use of document media, PowerPoints and learning videos in learning is proven to increase the effectiveness of distance learning, which is seen from the increase in learning completeness obtained by students from the initial conditions of 32.14% to 85.71% in cycle I and increased to 95.14% in cycle II or in the final condition, there was an increase of 63% from the initial condition.